Lukács and mimesis: representations, reflections, and literary creation - Ledesma de la Fuente, Álvaro (Revista de Filosofía, 2026)
Mimesis, understood as a representation of reality and a central axis of aesthetic reflection, finds a particularly influencial formulation in the work of György Lukács. This article explores its development in The Theory of the Novel and Aesthetics and places this ideas in dialogue with those proposed by Erich Auerbach and Lubomír Doležel, who interpret it from different angles: the narrative practices of each era and posible worlds theory. From this perspective, mimesis is presented not only as a reflection of reality, but also as an active process of reconstruction and literary creation.